Impact of Product Prices to the Food Choice of Customers in Pizza Hut Store at SM San Jose Delmonte Bulacan: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Developing customer satisfaction is regarded as being the highest possible priority forbusiness success. Therefore, it's important to determine the variables that influence customersatisfaction. In the casual restaurant sector of the Philippine market, this paper will examinewhether product quality, pricing equality, and product discounts impact customer satisfaction.The results showed that for a casual restaurant's good service to generate brand loyalty, itsprimary focus should be on product quality compared to pricing, especially regarding taste,freshness, and value. The results also showed that environmental factors and price fairnesssignificantly increase consumer contentment. These findings offer policymakers in casualindustry restaurants useful suggestions and recommended procedures.Food is an essential factor that the world needs the most. It has a great effect from a macroperspective to a micro perspective point of view. It is needed in able for the economy to haverevenues from exportation to transactions inside a country’s premises, and it is also neededfor every family in order for them to survive in their everyday lives. The major effect of foodprices in the market is the inflation rate.
Keywords: Business